Study of Turkic Root Words in Turkology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
in this article, the analysis of the issue of Turkish root words recognized in Turkology is mentioned. In 2017, the "Fan" publishing house published a major work by Professor M. Mirtojiyev entitled "Research of Turkish root words". This book can be recognized as the most important resource created not only in Uzbek linguistics, but also in world linguistics, particularly in Turkology. After this book was published, German linguists from Germany offered the professor to translate the book into German together. However, M. Mirtojiyev did not accept this offer due to his age and busy schedule (from conversations with M. Mirtojiyev).